1984
DOI: 10.1177/109019818401100402
|View full text |Cite
|
Sign up to set email alerts
|

An Application of the Health Belief Model Toward Educational Diagnosis for VD Education

Abstract: A protocol is developed which allows the translation of the Health Belief Model (HBM) to practice in supplying empirical needs assessment data on which to build responsive and effective VD education. The HBM is recognized as among the most important theoretical formulations to explain health behavior available in the health education literature, although there has to date been no information as to how to bridge the gap between theory and practice for actual, specific, and detailed programmatic input. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 27 publications
3
29
1
Order By: Relevance
“…With the emergence of HIV/AIDS and its sexual transmission, health beliefs have been examined as predictors of risk reduction in college students (Simon and Das, 1984;Basen-Engquist, 1992). The majority of research has targeted specific risk behaviors in isolation, but there has been little research which attempted to understand variables which influence the practice of multiple risk behaviors which potentially heighten exposure to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of HIV/AIDS and its sexual transmission, health beliefs have been examined as predictors of risk reduction in college students (Simon and Das, 1984;Basen-Engquist, 1992). The majority of research has targeted specific risk behaviors in isolation, but there has been little research which attempted to understand variables which influence the practice of multiple risk behaviors which potentially heighten exposure to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of care seeking for STDs, the HBM assumes that the desire to reduce the physical consequences (severity) of the symptoms or disease is related to a person's positive inclination to maintain good reproductive health [3]. As such, the higher a person's perceived seriousness about his/her symptoms, the more quickly he/she would be expected to seek STD-related care.…”
mentioning
confidence: 98%
“…One of the most widely used frameworks in the literature on health-seeking behavior for STDs is the Health Belief Model (HBM) [2][3][4][5][6]. The HBM attempts to predict healthrelated behavior by focusing on the attitudes and beliefs of individuals [7].…”
mentioning
confidence: 99%
“…Perceived barriers has been found to be significantly related to preventive health behaviors in the influenza and swine flu studies (Aho, 1979;Cummings, Jette & Brock, 1979;Rundall & Wheeler 1979), Langlie's (1977) behaviorally consistent group of preventive health behaviors, preventive sexually transmitted disease checkups (Simon & Das, 1984), and high blood pressure screening (King, 1982). In addition, a study of 30 post coronary artery bypass patients (Tirrell & Hart, 1980) found barriers to be the only HBM component predictive of compliance with an individualized prescribed exercise regimen.…”
Section: Barriersmentioning
confidence: 99%
“…This is particularly true in relation to behaviors which are on-going or more complex. For example, Simon and Das (1984) …”
Section: Benefitsmentioning
confidence: 99%